The world in six songs [how the musical brain created human nature] - Levitin, Daniel J. (New York : Penguin Audio, 2008)
Analyzes six evolutionary musical forms while identifying neural impulses that reflect the brain's development in accordance with music, illuminating the sophisticated biological process that accompanies the musical experience.
Subtitle from container.
Abridged.
Compact disc.
Read by the author.
Keywords: Music -- Psychological aspects; Music -- Social aspects; Music -- Origin; Compact discs; Audiobooks